The Phospholipid Degradation in Paddy Rice: a Theoretical Model with DFT/B3LYP 6–311 G - Bamba, EL Hadji Sawaliho; Koffi, Alain Koffi; N’Guessan, Boka Robert (European Journal of Applied Sciences, 2021)
This work focuses on the degradation of phospholipids during rice storage. It aims to identify the chemical phenomena underlying this process. It aspires to test the hypothesis that 1-palmitoyl-2-oleoyl-sn-glycero-3-phosphocholine (PC) triggers the latter. It uses the Density Functional Theory (DFT) at the B3LYP/6–311 G level in this sense. The research evaluates the reactivity of phospholipids; it estimates the orbital frontier energies. It assesses its global index. It determines the dual descriptors. It measures the molecular electrostatic potential. It calculates the thermodynamic quantities related to phospholipids formation. It discusses these results before concluding. The energies of the orbital frontier establish that 1-palmitoyl-2-oleoyl-sn-glycero-3-phosphoethanolamine (PE) is more reactive than PC. In other words, PE is the precursor of lipid alteration. The work highlights the parts of PE likely to join this transformation. This research demonstrates that PE reacts with its C=O (sp2) or C-O (sp3)-C oxygen or its phosphorus P2 when it associates with a nucleophilic entity. For an electrophilic attack, it interacts with its hydrogen and its nitrogen or its C92 carbon (sp2). These sites can promote its deterioration during rice storage.